Optimization of extraction process and antioxidant activity of total flavonoids from sauce-flavor Baijiu distiller's grains - LI Fangxiang, TANG Jiale, YU Zhengtao, WANG Guiyuan, XIE Yi (Zhongguo niangzao)
Using the byproduct distiller's grains of sauce-flavor (Jiangxiangxing) Baijiu in Renhuai city, Guizhou province as the research object, the ethanol as the extract solvent, the total flavonoids were extracted by water bath reflux. Using total flavonoids yield from distiller's grains as the response value, the extraction process was optimized by single factor tests and Box-Behnken response surface tests, and the antioxidant activity was measured. The results showed that the optimal process conditions for the extraction of total flavonoids from the distiller's grains by ethanol extraction method were as follows: ethanol volume fraction 80%, solid and liquid ratio 1∶23 (g∶ml), extraction time 29 min, and water bath temperature 72 ℃. Under these optimal conditions, the yield of total flavonoids in the distiller's grains of sauce-flavor Baijiu was 4.02%. The antioxidant tests results showed that the semi- inhibitory concentration (IC50) values of total flavonoids extract on 1,1-diphenyl-2-picrohydrazyl (DPPH) radicals and hydroxyl radicals were 18.89 μg/ml and 14.69 μg/ml, respectively, indicating that the total flavonoids extract from sauce-flavor Baijiu had certain antioxidant activity, and provided a theoretical basis for the preparation of flavone-rich blended liquor.